Microbial Symphony: Understanding Biochemical Pathways for Precision Medicine and Beyond - Dr B Sheshu Kumar; Dr. A. Mrudula Srinivasulu (International Journal of Antibiotics, 2024)
The human microbiome, an intricate ecosystem of microorganisms inhabiting the body, is a key regulator of host biochemistry and physiology. This review delves into the complex biochemical pathways influenced by the microbiome, spotlighting critical metabolites like short-chain fatty acids, bile acids, and tryptophan derivatives, which impact immune regulation, energy metabolism, and neurobehavioral functions. By examining interactions between the microbiome and the host, including the influence of genetic factors and metabolite-driven communication networks, this work underscores the microbiome's pivotal role in sustaining health and its involvement in the development of diseases such as metabolic disorders, cancer, and neurological conditions. Recent advancements in multi-omics technologies, synthetic biology, and AI-driven analytics have significantly advanced microbiome research. These innovations have facilitated the discovery of novel biomarkers, the creation of microbiome-targeted therapies, and the engineering of synthetic microbial communities for therapeutic purposes. The review also highlights the expanding relevance of non-gut microbiomes—such as those in the skin, oral cavity, and respiratory system—and their systemic impacts, broadening the traditional scope of microbiome research. By integrating historical milestones, current progress, and future opportunities, this review emphasizes the transformative potential of microbiome science in diagnostics, therapeutics, and biotechnological applications. Addressing unresolved issues, including inter-kingdom dynamics, environmental factors, and the need for regulatory frameworks, is essential to fully leverage the microbiome's capabilities. Ultimately, this review positions the microbiome as a cornerstone of precision medicine, paving the way for innovative approaches to chronic disease management, health optimization, and solutions to global sustainability challenges.
Keywords: Biomarkers; Diagnostics; Human microbiome; Precision medicine; SCFAs; Synthetic Biology; bile acids; energy metabolism; immune modulation; multi- omics